Pemanfaatan Limbah Ikan Menjadi Pakan Ikan Pada Masyarakat Pesisir: Pemanfaatan Limbah Ikan Menjadi Pakan Ikan Pada Masyarakat Pesisir - Nurul Eka Wijayanti Risa; Aam Azatil Isma (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2023)
Fish waste is often found in coastal areas due to high fishing activity in the area. Fish waste is found in the form of remains of internal organs, head bones, scales, and crab shells. The handling of fish waste in Lamurukung Village has not been carried out properly so there is a need to increase knowledge in processing fish waste into products. Community service activities aim to educate the public about processing fish waste into fish feed. From the results of the activities carried out, it was obtained an increase in public knowledge in processing fish waste into fish feed